Urban Gas and Electricity Networks in Portugal: Competition and Collaboration (1850-1926) - Matos, Ana Cardoso de (2012)
In the last decades of the nineteenth century, even though the decision to create urban infrastructures for gas was one of the responsibilities of local councils, the concession for gas distribution was granted to private businesses right from the very beginning. In an attempt to attract private capital, the concessions granted by the municipal councils were for extended periods of time, in order to allow for the recovery of the fixed capital investment. Thus, at the beginning of the twentieth century, the introduction of electricity was hampered by those extended contracts established by municipal councils with gas companies to supply gas for public lighting. This situation explains why electricity was often introduced earlier in cities that were not district capitals and did not have gas lighting. This study will trace the diffusion of gas urban networks in Portugal in comparison with those of electricity, and it will also analyse some situations of competition or cooperation in the creation and exploitation of gas and electricity networks.